2013
DOI: 10.1007/s11434-013-5832-0
|View full text |Cite
|
Sign up to set email alerts
|

Labelling of a pyrazole derivative with 131I and investigation of its radiopharmaceutical potential

Abstract: We investigated the radiolabeling efficiency, in vitro stability, and biodistribution of radioactive iodine ( 131 I)-labeled 4-benzoyl-1-(4-carboxyphenyl)-5-phenyl-1H-pyrazole-3-carboxylic acid (P3CA). A quality-control study of the labeled substance ( 131 I-P3CA) was conducted using electrophoresis and radio thin-layer chromatography (RTLC). Biodistribution studies were undertaken in 9 female albino Wistar rats. Rats were killed at various times (15, 60 and 180 min), their organs removed, and percentage of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In the study reported by Kurtdede et al., 131 I‐labeled 4‐benzoyl‐1‐(4‐carboxyphenyl)‐5‐phenyl‐1H‐pyrazole‐3‐carboxylic acid (P3CA) was studied, and in vivo studies were performed on Albino Wistar rats. According to the results, the maximum uptake of 131 I‐P3CA was seen in lungs, stomach, and spleen at 15 min . Haque et al.…”
Section: Resultsmentioning
confidence: 89%
“…In the study reported by Kurtdede et al., 131 I‐labeled 4‐benzoyl‐1‐(4‐carboxyphenyl)‐5‐phenyl‐1H‐pyrazole‐3‐carboxylic acid (P3CA) was studied, and in vivo studies were performed on Albino Wistar rats. According to the results, the maximum uptake of 131 I‐P3CA was seen in lungs, stomach, and spleen at 15 min . Haque et al.…”
Section: Resultsmentioning
confidence: 89%